Manufacturing Transformation: Comparative Studies of Industrial Development in Africa and Emerging Asia - Carol Newman; John Page; John Rand; Abebe Shimeles; Måns Söderbom; Finn Tarp (Oxford University Press, 2016)
While it is possible for economies to grow based on abundant land or natural resources, more often structural change—the shift of resources from low-productivity to high-productivity sectors—is the key driver of economic growth. Structural transformation is vital for Africa. The region's much-lauded growth turnaround since 1995 has been the result of fewer economic policy mistakes, robust commodity prices, and new discoveries of natural resources. At the same time, Africa's economic structure has changed very little. Primary commodities and natural resources still account for the bulk of exports. Industry is most often the leading driver of structural transformation. Africa's experience with industrialization over the past thirty years has been disappointing. In 2010, sub-Saharan Africa's average share of manufacturing value added in GDP was 10 per cent, unchanged from the 1970s. In fact the share of medium- and high-tech goods in manufacturing production has been falling since the mid-1990s. Per capita manufactured exports are less than 10 per cent of the developing country average. Consequently, Africa's industrial transformation has yet to take place. This book presents results of comparative country-based research that sought to answer a seemingly simple but puzzling question: why is there so little industry in Africa? It brings together detailed country case studies of industrial policies and industrialization outcomes in eleven countries, conducted by teams of national researchers in partnership with experts on industrial development. It provides the most comprehensive description and analysis available of the contemporary industrialization experience in low-income Africa.
Keywords: 330; Africa; industrial development; economic growth; structural transformation; natural resources